Website Quality Analysis Using WebQual 4.0, Customer Satisfaction Index, and Importance Performance Analysis - Adhigamika, Dewa Putu Surya; Pratama, I Putu Agus Eka; Raharja, I Made Sunia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2024)
The development of technology is currently growing rapidly in various aspects of human life, including in the field of education such as the creation of academic information systems. The study aims to analyze the quality of service on the SISAKTI-NG website based on user expectations and website performance. Question indicators in making questionnaires refer to three dimensions, namely: usability, information quality and interaction quality in the WebQual 4.0 Method by distributing questionnaires to 100 respondents. Analysis of website quality using the Customer Satisfaction Index Method to analyze satisfaction with SISAKTI-NG services and the Importance Performance Analysis Method to analyze the quality of SISAKTI-NG services and obtain indicators that require improvement and are maintained based on the perceptions and expectations of website users. The results show that the satisfaction of SISAKTI-NG website users is